Macroscale Superlubricity Achieved With Various Liquid Molecules: A Review - Ge, Xiangyu; Li, Jinjin; Luo, Jianbin (Frontiers in Mechanical Engineering, 2019)
Superlubricity is generally classified as solid superlubricity and liquid superlubricity according to the lubricants involved at the interfaces, and is a popular research topic in tribology, which is closely linked to energy dissipation. Significant advancements in both experimental studies and theoretical analysis have been made regarding superlubricity in the past two decades. Compared with solid superlubricity, liquid superlubricity has many advantages; e.g., it is more easily achieved at the macroscale and less sensitive to the surface smoothness and atmospheric conditions. In the present study, the advancements in liquid superlubricity at the macroscale are reviewed, and the corresponding mechanisms for various types of liquid lubricants are discussed. This investigation is important for engineering traditional mechanical lubricating systems. Finally, the issues regarding the liquid superlubricity mechanism and the future development of liquid superlubricity are addressed.